Educating Renewable Energy Innovation: Bio-Briquette Development from Plantation Waste in South Toapaya, Bintan Island - Aditia Ayu Rahma Nabila; Aidil Mersa Fatiha; Deny Nusyirwan; Firman Apriansyah; Ahmad Rusdy; Muhamad Al Rasyid; Zuleriwati AS; Abdul Alimul Karim; Rafi Dio (Andalasian International Journal of Applied Science, Engineering and Technology, 2026)
The increasing demand for energy and the continued reliance on fossil fuels in Indonesia present serious environmental and economic challenges. This community service project introduces an innovative solution by developing bio-briquettes from cassava peel waste in South Toapaya Village, Bintan Island. The program applies a Participatory Action Research (PAR) approach to engage the community in a hands-on learning experience, from problem identification to production and evaluation. Through interactive socialization and technical training, villagers—especially farmers and housewives—were educated on the benefits of converting plantation waste into renewable energy. The process involved drying, pyrolysis, mixing with natural adhesives, molding, and testing of the resulting briquettes. The produced bio-briquettes demonstrated effective burn duration up to 42 minutes with low smoke output, making them a viable alternative to firewood. This initiative not only reduced organic waste but also empowered the community to create economic value from local resources. While the project achieved its educational and technical goals, limitations included a lack of laboratory validation and small-scale outreach. The results show promising potential for broader implementation in rural energy innovation.